Reaction of Diazo Compounds with Difluorocarbene: An Efficient Approach towards 1, 1‐Difluoroolefins. (19th November 2015) - Zhang, Zhikun; Yu, Weizhi; Wu, Chenggui; Wang, Chengpeng; Zhang, Yan; Wang, Jianbo
Abstract: A transition‐metal‐free difluoromethylenation of diazo compounds that proceeds under mild conditions has been developed and is based on the use of TMSCF2 Br as the difluoromethylene source and tetrabutylammonium bromide (TBAB) as the promoter. The chemoselective formal carbene dimerization reaction is achieved owing to the electronic properties and the relative stability of the difluorocarbene intermediate.